ANALYSIS OF MHD MIXED CONVECTION FLOW PAST A STRETCHING SHEET IN POROUS MEDIUM - Ritu; Verma, Praneeta; Poply, Vikas (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In this study, we are examining the combined effects of magnetohydrodynamics (MHD), with mixed convective flow over a linearly stretching sheet imbedded in a porous medium. The mathematical formulation utilizes appropriate similarity transformations to generate a system of coupled, nonlinear ordinary differential equations (ODEs) that are influenced by important physical parameters on velocity, temperature, and concentration fields. The Runge-Kutta-Fehlberg (RKF) method is employed to numerically solve these ODEs. The dimensionless velocity, and temperature profiles are graphically illustrated and discussed in detail in relation to the effects of a variety of governing parameters, such as the magnetic parameter, Eckert number, and porosity parameter. Potential applications in industrial, chemical, and engineering processes are provided by the results, which offer valuable insights into the behavior of MHD flows in porous media environments.